Unravel the regulatory mechanism of Yrr1p phosphorylation in response to vanillin stress in Saccharomyces cerevisiae - Weiquan Zhao; Xinning Wang; Bolun Yang; Ying Wang; Zailu Li; Xiaoming Bao (Microbial Cell Factories, 2023)
Abstract Improving the resistance of Saccharomyces cerevisiae to vanillin, derived from lignin, will benefit the design of robust cell factories for lignocellulosic biorefining. The transcription factor Yrr1p mediates S. cerevisiae resistance to various compounds. In this study, eleven predicted phosphorylation sites were mutated, among which 4 mutants of Yrr1p, Y134A/E and T185A/E could improve vanillin resistance. Both dephosphorylated and phosphorylated mutations at Yrr1p 134 and 185 gathered in the nucleus regardless of the presence or absence of vanillin. However, the phosphorylated mutant Yrr1p inhibited target gene expression, while dephosphorylated mutants promoted expression. Transcriptomic analysis showed that the dephosphorylated Yrr1p T185 mutant, under vanillin stress, upregulated ribosome biogenesis and rRNA processing. These results demonstrate the mechanism by which Yrr1p phosphorylation regulates the expression of target genes. The identification of key phosphorylation sites in Yrr1p offers novel targets for the rational construction of Yrr1p mutants to improve resistance to other compounds.